2000
DOI: 10.3171/spi.2000.93.2.0252
|View full text |Cite
|
Sign up to set email alerts
|

In vitro biomechanical analysis of three anterior thoracolumbar implants

Abstract: Object. The goal of this study was to evaluate the comparative efficacy of three commonly used anterior thoracolumbar implants: the anterior thoracolumbar locking plate (ATLP), the smooth-rod Kaneda (SRK), and the Z-plate. Methods. In vitro testing was performed using the T9—L3 segments of human cadaver spines. An L-1 corpectomy was performed, and stabilization was achieved using o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 27 publications
0
26
0
4
Order By: Relevance
“…However, these are expensive alternatives, and there is a lack of long-term results considering the osseointegration of these spacers with mounted cancellous bone, sintering and loosening. For the most part, only primary stability tests have been presented [1,7,11,12,20,23,28]. Good long-term results with strut grafting and anterior stabilization were published only by Kaneda [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these are expensive alternatives, and there is a lack of long-term results considering the osseointegration of these spacers with mounted cancellous bone, sintering and loosening. For the most part, only primary stability tests have been presented [1,7,11,12,20,23,28]. Good long-term results with strut grafting and anterior stabilization were published only by Kaneda [15].…”
Section: Discussionmentioning
confidence: 99%
“…The search for an alternative reconstruction material is still under way and ranges from the use of fibula via rib segments to titanium bodies for vertebral body replacement [7,9,11,12,17,18,20,28,30]. Problems include cost, lack of long-term results concerning osseointegration and sintering, loosening and mechanical failure of spacers.…”
Section: Introductionmentioning
confidence: 99%
“…The maximum loading levels were within the range of those reported in previous biomechanical studies involving lumbar reconstruction models. 1,11,13,14,23 Because pilot studies demonstrated that load-displacement and load-strain or pressure data after the second load-unload cycle were almost identical, the loading procedure involved the application of three load-unload cycles. The third loading cycle was used to allow for data analysis of all biomechanical parameters.…”
Section: Specimen Preparation and Biomechanical Testingmentioning
confidence: 99%
“…The specimen was allowed to "creep" for 30 seconds between load application and data collection. 13,14,23 Two-level fusion was simulated at L5-6 and L6-S1. The L4-5 level was defined as the superior adjacent segment.…”
Section: Specimen Preparation and Biomechanical Testingmentioning
confidence: 99%
“…1,5,14,15 Biomechanical studies have compared anterior with posterior instrumentation in the bovine spine, 3 as well as compared various anterior instrumentation systems, with the anterior 2-rod system being the most stable. 2,4,[6][7][8] In recent years expandable cages have become an increasingly common method of reconstructing the anterior column. Advantages include ease of deployment, induction of an axial loading force on the bodies above and below theoretically enhancing fusion rates, and ability to better preserve the adjacent endplates.…”
mentioning
confidence: 99%